How to supervise people technique for getting results through others - Brown, Rick; Jack Wilson and Associates Inc. ([S.l.] : JWA, 2000)
This program shows the techniques to develop and inspire people
Executive producer, Jack Wilson
Narrator, Eileen Parkinson
Keywords: Supervision of employees -- Handbooks, manuals, etc